2014
DOI: 10.1007/s12281-014-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Echinocandin Resistance in Candida

Abstract: Echinocandins are the newest antifungal agents approved for use in treating Candida infections in the US. They act by interfering with 1,3-β-D-glucan synthase and therefore disrupt cell wall production and lead to Candida cell death. There is no intrinsic resistance to echinocandins among Candida species, and isolates from historic collections archived before the release of the echinocandins show no resistance. Resistance to the echinocandins remains low among most Candida species and ranges overall from 0–1%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
2
12
1
1
Order By: Relevance
“…Echinocandin resistance associated with crossresistance of azoles was reported in C. glabrata (36). The current results are in concordance with the data for a low rate of echinocandin resistance in C. albicans (22,37,38). Shokohi et al (39) detected two (4.6%) caspofungin resistant strains among 44 isolates.…”
Section: Discussionsupporting
confidence: 90%
“…Echinocandin resistance associated with crossresistance of azoles was reported in C. glabrata (36). The current results are in concordance with the data for a low rate of echinocandin resistance in C. albicans (22,37,38). Shokohi et al (39) detected two (4.6%) caspofungin resistant strains among 44 isolates.…”
Section: Discussionsupporting
confidence: 90%
“…While MDR is not a common phenotype among fungal pathogens, it was reported earlier in C. glabrata, with simultaneous acquisition of resistance to echinocandins and to azoles and separate acquisition of resistance to 5-FC (37). In the United States, a significant proportion (30% to 40%) of echinocandin-resistant isolates are also resistant to azoles (38,39). While a recent study (40) suggested an association between MDR and the use of echinocandins and azoles, another investigation (41) described MDR to echinocandins, azoles, and amphotericin B in C. glabrata isolates recovered from a neutropenic patient with prolonged fever.…”
Section: Discussionmentioning
confidence: 88%
“…A new class of drugs, the echinocandins, has been shown to have fungicidal effects in all Candida species ( Nett and Andes, 2016 ). The echinocandins include caspofungin, micafungin, and anidulafungin ( Grossman et al, 2014 ; Koehler et al, 2014 ; Paramythiotou et al, 2014 ). Echinocandins inhibit (1,3) β- D -glucan synthase, thereby preventing glucan synthesis, which is present in the cell membrane of fungi ( Figure 1 ).…”
Section: Traditional Agents and Mechanisms Of Actionmentioning
confidence: 99%
“…This class of drugs has certain advantages attributable to its effects on the fungal cell wall, including a lower risk of side effects since animal cells do not have this structure. Further, echinocandins can be used in cases of azole-antifungal resistance ( Spampinato and Leonardi, 2013 ; Grossman et al, 2014 ; Maubon et al, 2014 ; Paramythiotou et al, 2014 ).…”
Section: Traditional Agents and Mechanisms Of Actionmentioning
confidence: 99%